Problems of identifying and regulating the structure of the labour market in depressive Lithuanian regions - Šileika, Algis; Andriušaitiene, Daiva (Journal of Business Economics and Management, 2006)
In order to identify labour market problems in the depressive regions of Lithuania and to provide guiding lines in the search for their solution, it is necessary to conduct a systematic analysis of the structure of employable population encompassing the characteristics of segments of employed and unemployed persons as well as individuals not registered with the official labour market. Correlation and factor analysis of eighteen macroeconomic indicators investigating into indicators of all municipalities of the country and depressive regions separately (20 municipalities where the unemployment rate exceeded the average in the country by 1,5 times in 2004) enabled evaluation of the significance of employment and unemployment indicators as well as impact thereof on other indicators chosen for the analysis to feature the trends of social and economic development on national level and in depressive regions in 1996–2004. Apart from special sociological research, characterization of the structure and peculiarities of labour force is confined to assumptions of logical analysis, but the invented technologies give grounds to maintain that dynamics of the employment indicator reflects the trends and outcomes of the development of economic activities only to a certain limited extent. Relation of the unemployment indicator, particularly that of long‐term unemployment, with other macroeconomic indicators is much tighter. However, as we can see from the analysis, relevantly big share of employable individuals not participating in the labour market has been little analysed by the structure, though most probably this share consists of the following basic groups: unemployed “volunteers”, “labour migrants”, unofficially employed individuals and persons employed in in‐kind farms. Yet, the analysis of statistical data shows that this is not an idiosyncrasy of depressive regions of the country. In the analysis of the structure of the labour market, the following problems extremely important in the depressive regions of Lithuania may be singled out: long‐term unemployment trap determines emigration of youth and better skilled labour force; consequently this results in prevalence of senior and pension‐age population, unskilled labour force and out‐of‐skill individuals in the structure of employable population, and in unofficial, ineffective “survival” employment in small, quasi‐in‐kind farms that have become a traditional way of life of rural population.Firstd Published Online: 14 Oct 2010